Effect of Gratitude on Benign and Malicious Envy: The Mediating Role of Social Support - Xiang, Yanhui; Chao, Xiaomei; Ye, Yanyan (Frontiers in Psychiatry, 2018)
Gratitude has been investigated in various areas in psychology. The present research showed that gratitude had some positive effects on aspects of our life, such as subjective well-being, life satisfaction, and social relationships. It can also help us relieve negative emotions. However, the existing literature has not studied the influence of gratitude on envy. The present study used structural equation modeling to test the mediating role of social support between gratitude and two types of envy (malicious and benign). We recruited 426 Chinese undergraduates to complete the Gratitude Questionnaire, Malicious and Benign Envy scales, and the Multi-Dimensional Scale of Perceived Social Support. Results showed that gratitude positively predicted benign envy and negatively predicted malicious envy. In addition, the indirect effect of gratitude on two kinds of envy via social support was significant. These results revealed the direct relationship between gratitude and malicious and benign envy, and the mediating effect of social support, which will help find effective measures to inhibit malicious envy and promote benign envy from the perspective of cultivating gratitude and increasing individuals’ social support.